Hubungan Pengetahuan, Sikap dan Dukungan Keluarga terhadap Kelengkapan Imunisasi Dasar pada Balita Usia 24-36 Bulan - Rismaya, Lilis (SIMFISIS Jurnal Kebidanan Indonesia, 2024)
Introduction: In terms of immunization, the Palabuhanratu Community Health Center is still far from the target of 90%. If a child is infected with a virus or other infectious disease, this could trigger a pandemic or other extraordinary event (KLB).Objective: To determine the relationship between knowledge, attitudes and parental support regarding vaccination in the Sukabumi area served by the Palabuhanratu Community Health Center.Method: This research uses a quantitative correlational research approach. This study used a cross-sectional design. A total of 685 newborns and their mothers participated in the study; 88 people were selected randomly using the Proportionate Stratified Random Sampling sampling technique. The instrument uses a questionnaire and the data collected is then statistically tested using the chi-square test.Results: Based on the chi-square statistical test, it was found that there was a relationship between maternal knowledge (P-value 0.005), family attitudes (P-value 0.001 and an Odds Ratio value of 9.317 (1.958 – 44.337) and family support (p-value 0.001) with immunization. complete basics in toddlers aged 24-36 years. Conclusion: There is a significant relationship between maternal knowledge, maternal attitudes and family support with providing complete basic immunization to toddlers aged 24-36 months in the work area of ​​the Palabuhanratu Community Health Center.